Delivering Optometric Graduates Ready for Practice Beyond the Cities and Ready to Serve an Ageing Population. - Junghans, Barbara; Jacobs, Robert; Hendicott, Peter; Cochrane, Anthea; Palagyi, Anna (Australian Learning and Teaching Council (ALTC), 2011)
Report from a project that aimed at a definition of pedagogically sound future directions for enhancing the student experience relating to delivering optometric graduates who are prepared and keen to work in the rural sector, and/or with low vision patients. A consortium of optometric educators from all schools of optometry in Australia and New Zealand (1) conducted worldwide benchmarking across a range of health care disciplines of current pedagogical practice in preparing students for work in rural areas and with special populations; (2) sought input from the profession regarding the optometric needs of the rural and special population sector and the potential role and requirements of optometrists in practice acting as preceptors; and (3) produced a Compendium of Learning Activities and a "Future Directions" statement reflecting educational best practice.